Efficacy of deep brain stimulation in treating monogenic dystonia symptoms: protocol for a systematic review - Sylvia Boesch; Rocio Rodriguez-Lopez; Beatriz Carmona-Hidalgo; Javier Quintero; Juan Antonio Blasco-Amaro; Carola Reinhard (BMJ Open)
Introduction Complexity leads to some dystonias being considered as rare diseases with scarce synthesised evidence. Despite the deficit of scientific evidence, deep brain stimulation (DBS) is currently an effective treatment for dystonias using different brain targets, providing significant improvement of dystonic symptoms regardless of their cause. However, there is considerable variability and non-response rate due to factors such as classification, semiology, duration, aetiology and genetic cause of the disease. This protocol presents the methodology of a planned systematic review to assess the efficacy of DBS as a treatment for monogenic dystonia symptoms, a broad spectrum of pathogenic dystonias due to variants in single genes not yet explored.Methods and analysis This protocol follows the Preferred Reporting Items for Systematic review and Meta-Analysis Protocols guidelines. With the aim to test the efficacy of DBS in monogenic dystonias, the research question in population, intervention, comparator and outcomes format will cover patients with monogenic dystonia treated with DBS with a minimum of 3 months' follow-up after surgery. The outcomes will be assessed using generic and specific scales to measure the efficacy and safety of the intervention. The search will be performed in generic and specific databases and bibliographic resources from 2000. We will include systematic reviews, randomised controlled trials and primary studies in English. In this protocol, the initial search strategy in MEDLINE is presented. Additionally, the protocol provides a description of the prospective assessment of the risk of bias in the selected studies. If studies appear homogeneous and the sample of patients is sufficiently large, a meta-analysis and a subgroup analysis are planned.Ethics and dissemination Ethics committee approval is not required. The results of the review will be published through an open access journal.PROSPERO registration number CRD42023448145